Happy End - Lipský, Oldřich 1924-1986; Macourek, Miloš 1926-2002; Novotný, Vladimír 1914-1997; Menšik, Vladimír 1929-1988; Obermaierová, Jaroslava; Abrhám, Josef 1939-2022 (Second Run, 2024)
A dark comedy about a murder and its consequences presented in a backwards manner, where death is actually a rebirth. The film starts with an "execution" of the main protagonist and goes back to explore his previous actions and motivations. [www.imdb.de]
Spielfilm. Tschechoslowakei. 1967
Bildformat: 1,37:1
Keywords: Film; DVD-Video